Low antiretroviral therapy uptake and low early retention among pregnant women who tested positive for human immunodeficiency virus in informal health centers in urban and semi-rural settings in Cameroon: a prospective cohort study - Audrey Amboua Schouame Onambele; Audrey Amboua Schouame Onambele; Francis Yuya; Arielle Andtoungou Schouame; Sylvie Kwedi Nolna; Sylvie Kwedi Nolna; Antoine Socpa (Frontiers Media S.A., 2023)
IntroductionDespite the efforts of Cameroon's Ministry of Public Health against informal health centers (IHCs) because of their illegitimacy, the number of IHCs is increasing in Cameroon. Most of these IHCs have antenatal care services and screen pregnant women for HIV. However, nothing is known about the subsequent outcomes of those who tested positive for HIV. This study aimed to assess the initiation of antiretroviral therapy (ART) in ART-naïve pregnant women screened HIV positive in IHCs within three months of diagnosis and their ART retention at three months post-initiation. In addition, we sought to identify the factors associated with ART non-initiation in this population.MethodsMay 01, 2019 to August 31, 2020, we carried out a prospective cohort study of ART-naïve pregnant women who attended their first antenatal care visit and screened HIV positive at IHCs in the cities of Douala and Ebolowa in Cameroon. Standardized questionnaires were used to interview consenting participants at three points: the day of the delivery of the antenatal HIV test result, three months later, and three months after ART initiation. The data collected were entered into KoboCollect and analyzed using SPSS V23.0 software. The Chi-square test was used to compare proportions, Kaplan Meier techniques and Cox proportional hazards regression was used to estimate retention in ART and identify factors associated with ART non-retention, respectively.Results and discussionA total of 85 ART-naïve pregnant women living with HIV were enrolled in the study. The median age and gestational age at the first antenatal care visit were 29 years (interquartile range (IQR), 2333.5) and 28weeks of amenorrhea (IQR, 2032), respectively. Only 34% (29/85) initiated ART, and 65.5% (19/29) of the initiators were retained in ART three months later. Lack of perceived self-efficacy to initiate ART (adjust Hazard Ratio = 5.57, 90% CI: 1.29 to 24.06), increased the probability of not be retaining in ART by any time during three months post initiation. Given the low ART uptake and the low retention in care among pregnant women living with HIV screened in IHCs, PMTCT policies in Cameroon should pay greater attention to this population, to facilitate their continuum of PMTCT care.